Keefektifan Aplikasi Podcast Spotify dalam Pembelajaran Keterampilan Menyimak pada Siswa Kelas X SMA PGRI Larangan - Novia Shafa Dwijayanti; Dyah Werdiningsih (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
Learning media is needed by teachers so that students can receive information or messages well. The Spotify application used is a podcast for listening skills in students. The purpose of this study was to determine the effectiveness of the Spotify podcast application as a medium for learning listening skills for students in the X grade of PGRI Prohibition High School. The research method used is the qualitative and quantitative mixture method. The bound variable is PGRI Prohibition High School X class students. Data collection techniques through interviews and distributing questionnaires. The data analysis technique uses a Likert scale. The results of the study on the learning medium in the form of podcast application Spotify obtained four answer indicators, namely (1) strongly agree obtained a score of 203, (2) agree obtained a score of 373, (3) disagree got a score of 37, and (4) strongly disagree got a score of 6. Therefore, this application is worth using when learning listening skills in the classroom.